Competing at altitude: Does natural altitude training or simulated live high: train low provide athletes with the best preparation? - Carr, A. J.; Garvican-Lewis, L. A.; Vallance, B. S.; Drake, A. P.; Saunders, P. U.; Humberstone, C. E.; Gore, C. J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Natural altitude training is considered optimal for competition at moderate altitude (2000-3000m) (Mazzeo, 2008), however it remains untested if the same is true at low altitude (600-2000m). Potentially, other altitude training methods such as simulated live high: train low (LHTL) could also facilitate effective acclimation and improved performance at low altitude. This study aimed to compare the effects of natural altitude training and simulated LHTL with a control group, on mean blood lactate concentration [La-], time to exhaustion (TTE) and endurance performance at low natural altitude (~1400m). Methods: Twenty-two elite-level, male (n = 15) and female (n = 7) racewalkers completed 14 days of either: low natural altitude (n = 7; living and training at 1380m in Thredbo, Australia); simulated LHTL (n = 7; 14h.d-1 at 3000m simulated altitude); or control (n = 8; living and training at 600m). A 5 x 2km race-walking performance test, and incremental treadmill test incorporating time to exhaustion (TTE) were performed at 1380m altitude Before and After the intervention. A oneway ANOVA was performed to determine differences between groups, with statistical significance set at p < 0.05. Magnitude-based inferences were used to analyse the likelihood of differences between groups exceeding the smallest worthwhile change (SWC) in each variable, which was set at 0.2 of the between-subject standard deviation at baseline. Results: There was a significant, post-intervention decrease in [La-] in both the natural altitude (p = 0.048) and simulated LHTL (p = 0.01) groups compared with control. For TTE, there were no significant differences between groups from Before to After, however the improvement in the simulated LHTL group compared with control was likely greater than the SWC. Similarly, race walking performance in the natural altitude group was likely improved from Before to After in comparison to control, a result that approached significance (p = 0.07). Discussion: Our findings suggest that either natural altitude training or simulated LHTL can provide both physiological and performance benefits to athletes competing at ~1400m altitude. Whilst natural altitude training at or near the race altitude remains the likely most beneficial option for athletes competing at altitude, simulated LHTL may provide an alternative method to achieve some level of acclimation prior to competition at low altitude.